1980
DOI: 10.1111/j.1365-2559.1980.tb02910.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing pattern of paraquat poisoning in man

Abstract: The clinical and pathological findings are described in 14 patients who died between 6 hours and 26 days after drinking paraquat. Respiratory failure and delayed pulmonary fibrosis have become the hallmark of this poison, but were not the common mode of death in this series. Toxic myocarditis, renal tubular necrosis and centrilobular liver cell damage were significant factors in the eight deaths which occurred within 5 days of paraquat ingestion. Similar abnormalities plus respiratory failure caused the two de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…These authors suggested that a rapid accumulation of PQ into the heart in the early stages of exposure may play an important role in acute death. Toxic myocarditis was also reported by other authors in humans as resulting from PQ intoxication [46], [47], [48]. Povoa et al [49] reported that cardiac toxicity due to PQ is frequent (40%).…”
Section: Discussionsupporting
confidence: 54%
“…These authors suggested that a rapid accumulation of PQ into the heart in the early stages of exposure may play an important role in acute death. Toxic myocarditis was also reported by other authors in humans as resulting from PQ intoxication [46], [47], [48]. Povoa et al [49] reported that cardiac toxicity due to PQ is frequent (40%).…”
Section: Discussionsupporting
confidence: 54%
“…In South-East Asia, chemicals such as paraquat, parathion, acetic acid used for rubber preparation and Opium, diazepum, barbiturate are also used for self destruction. A study in India has shown that dichlorvos (76% EC) is also used as injectable suicidal agent [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, las publicaciones en relación con la descripción de las lesiones histopatoló-gicas que aparecen en el hígado son mucho menos numerosas y aunque se han establecido a grandes rasgos las principales alteraciones microscópicas [4,5,6,7], la interpretación del desarrollo de las mismas así como sus características histopatológicas no concuerdan en muchos casos con las lesiones que se observan en el hígado de los sujetos que han muerto como consecuencia de la ingestión de paraquat.…”
Section: Introductionunclassified